2023
DOI: 10.35145/jabt.v4i1.119
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Style, Motivation, and Work Environment on Job Satisfaction and Employee Performance at the Environment and Hygiene Department of Pekanbaru City

Abstract: This study aims to analyze the influence of leadership style, motivation, and work environment on job satisfaction and employee performance at the Pekanbaru City Environment and Hygiene Service. This research is quantitative research by distributing questionnaires to respondents. The sample selection method in this study used the census method so the sample in this study amounted to 58 respondents. Data analysis using Structural Equation Modeling (SEM) using the SmartPLS 3 application. The results of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…It is proven that there a relationship between motivation and job performance among public sector employees, which the employee has a good motivation, the job performance can be increase. The studies such as (Syamsir, 2020;Stefurak et al, 2020;Uka & Prendi, 2021;Schwarz et al, 2020;Maryani et al, 2021;Anisya et al, 2021;Almawali et al, 2021;Amha & Brhane, 2020;Mariana, 2020;Wahyudi et al, 2023;Sunarsi et al, 2021;Alam et al, 2021;Widarko & Anwarodin, 2022;Kurniasih et al, 2022;Adetola et al, 2022;Dharmanegara et al, 2021;Tenrisanna et al, 2021;Sudha et al, 2023;Kuswati, 2020;Riwukore et al, 2022;Riwukore et al, 2021: Ratnawati et al, 2020Niati et al, 2021;Suriyanti, 2020;Rivaldo, 2021;Sumaiti, 2021;Virgiawan et al, 2021;Sukhumvito et al, 2020;Noor et al, 2020;Al-Jedaia & Mehrez, 2020;Guo et al, 2021;Syaharudin et al, 2022;Andika & Darmanto, 2020). These findings may have consequences for the government, which has to recognise the value of employee motivation to boost output and enhance performance.…”
Section: Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is proven that there a relationship between motivation and job performance among public sector employees, which the employee has a good motivation, the job performance can be increase. The studies such as (Syamsir, 2020;Stefurak et al, 2020;Uka & Prendi, 2021;Schwarz et al, 2020;Maryani et al, 2021;Anisya et al, 2021;Almawali et al, 2021;Amha & Brhane, 2020;Mariana, 2020;Wahyudi et al, 2023;Sunarsi et al, 2021;Alam et al, 2021;Widarko & Anwarodin, 2022;Kurniasih et al, 2022;Adetola et al, 2022;Dharmanegara et al, 2021;Tenrisanna et al, 2021;Sudha et al, 2023;Kuswati, 2020;Riwukore et al, 2022;Riwukore et al, 2021: Ratnawati et al, 2020Niati et al, 2021;Suriyanti, 2020;Rivaldo, 2021;Sumaiti, 2021;Virgiawan et al, 2021;Sukhumvito et al, 2020;Noor et al, 2020;Al-Jedaia & Mehrez, 2020;Guo et al, 2021;Syaharudin et al, 2022;Andika & Darmanto, 2020). These findings may have consequences for the government, which has to recognise the value of employee motivation to boost output and enhance performance.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…However, study by Jufrizen et al (2021) found motivation is not a moderator in relationship between organizational culture and job performance. Most of studies shown that there a significantly positive relationship between motivation and job performance such as studies by (Syamsir, 2020;Schwarz et al, 2020;Stefurak et al, 2020;Uka & Prendi, 2021;Maryani et al, 2021;Anisya et al, 2021;Almawali et al, 2021;Amha & Brhane., 2020;Mariana, 2020;Wahyudi et al, 2023;Sunarsi et al, 2021;Alam et al, 2021;Widarko & Anwarodin, 2022;Kurniasih et al, 2022;Adetola et al, 2022;Dharmanegara et al, 2021;Tenrisanna et al, 2021;Sudha et al, 2023;Kuswati, 2020;Riwukore et al, 2022;Riwukore et al, 2021;Ratnawati et al, 2020: Niati et al, 2021Suriyanti, 2020;Rivaldo, 2021;Sumaiti, 2021;Virgiawan et al, 2021;Sukhumvito et al, 2020;Noor et al, 2020;Al-Jedaia & Mehrez, 2020;Guo et al, 2021;Syaharudin et al, 2022;Andika & Darmanto, 2020). Some studies such as Apex-Apeh et al (2020); Andika and Darmanto (2020); Sultana et al (2021); Noviani (2021) found that intrinsic motivation has significant influence on job performance, however extrinsic motivation does not have significant with job performance (Apex-Apeh et al, 2020).…”
Section: Research Objective 2 -Relationship Motivation and Job Perfor...mentioning
confidence: 99%
“…Kepuasan kerja berpengaruh terhadap kinerja karyawan (Mahardika et al, 2021). Kepuasan kerja berpengaruh positif dan signifikan terhadap kinerja karyawan (Wahyudi et al, 2023). Kurangnya peranan kepimpinan dalam mewujudkan komunikasi harmoni dan menyediakan panduan pekerja akan membawa kepada tahap prestasi pekerja yang rendah.…”
Section: Pendahuluanunclassified
“…When employees are happy in their careers, they are more likely to be motivated, engaged and committed to their work, leading to better job performance. Therefore, it is crucial for employers to create a work environment that fosters career happiness, which can ultimately lead to better business outcomes (Kumar & Pansari, 2016;Wahyudi et al, 2023;Yousuf & Saqib, 2021). this dependence, the Government of Oman has set a goal to achieve significant diversification through its Vision 2040 (Oman Government, 2020).…”
Section: Introductionmentioning
confidence: 99%